In vitro and in vivo studies of anti diabetic effect of khaya senegalensis leaves and bark extracts - Osman Widdat Allah, Marvit; Ahmed Alrasheid, Ayat; Suliman Elamin, Eltayeb (International Journal of Pharmacology and Toxicology, 2019)
Diabetes mellitus in Sudan is one of public health concern since it causes significant mortality and complications for long term. Though conventional drugs are used in the management of diabetes mellitus they are expensive, unavailable and also have numerous side effects. Khaya senegalensis has traditionally used in the management of diabetes. The present study was conducted to examine the In vitro and In vivo anti-diabetic activity of leaves and bark extracts of Khaya senegalensis. The leaves and bark of the plant were extracted with ethanol 96%, and then tested for anti-diabetic activity in a series of in vitro models and a type 2 diabetes model of rats. In vitro bark extract of k.senegalensis showed higher inhibitory activities against the enzyme with IC50 value 226.14 Âµg/ml. In vivo oral administration of the extracts of the k. senegalensis exhibited decrease in blood sugar level and was found to be time dependent. Bark extract showed strong in vitro and in vivo anti diabetic activity.Â Â